Vascular recanalization exacerbates BBB permeability after ischemic stroke - Wang, Rong-Fei; Liu, Jing; Chen, Chang-Hui (Frontiers in Neurology, 2025)
IntroductionIschemic stroke is a common and serious neurological disease. After cerebral ischemia occurs, the integrity of the BBB is disrupted, leading to increased permeability, causing pathophysiological changes such as brain edema and hemorrhagic transformation, which aggravates neuronal damage. Such changes become more obvious after the recovery of blood flow. However, the effect of vascular recanalization on blood–brain barrier leakage is poorly known.MethodsMice were divided into the recanalization group and the non-recanalization group. Mice in the recanalization group suffered from the middle cerebral artery occlusion and were reperfused 60 min later. Mice in the non-recanalization group suffered from permanent occlusion of the middle cerebral artery. The permeability of the blood–brain barrier was tested using fluorescence staining, and the expression of tight junction proteins and transcytosis-related proteins were analyzed by western blot.ResultsThe IgG results revealed a significantly larger area of leakage in the recanalization group compared to the non-recanalization group. A consistent trend was observed in the FITC-dextran leakage experiment. Moreover, after blood flow recanalization, there was a significant reduction in tight junctions-related proteins, occludin and ZO-1. Meanwhile, both ischemia and reperfusion caused changes in the ratio of transcytosis related protein Caveolin-1 /MFSD2a, and this is more obvious in the blood flow recanalization group.ConclusionVascular recanalization can exacerbate blood–brain barrier disruption, concurrently impairing both the paracellular and transcytosis pathways. This finding provides a rationale for exploring new approaches for protecting the integrity of the blood–brain barrier, reducing its permeability, and lowering the risk of hemorrhagic transformation.